Analysis of Letter of Intent and Its Implications on Unilateral Termination in Lease Agreement (Case Study of Decision Number 575/Pdt.G/2022/PN Jkt.Sel.) - Nawalia Azahra; Irsyaf Marsal (Jurnal Daulat Hukum, 2025)
This research aims to analyze the legal status of the Letter of Intent (LoI) within the Indonesian civil law system and its legal implications regarding unilateral termination in lease agreements. LoI is commonly understood as a preliminary document expressing initial intention and is generally considered non-binding. However, in practice, LoI may contain substantive clauses that create legal rights and obligations. This study employs a normative juridical method, utilizing statutory, conceptual, and case approaches, as seen in the South Jakarta District Court Decision No. 575/Pdt.G/2022/PN Jkt.Sel as the primary case study. The findings indicate that a LoI may possess binding legal force if it fulfills the essential elements of a valid contract under Article 1320 of the Indonesian Civil Code and has been partially or fully executed by the parties. The court decision establishes that unilateral termination of an LoI containing substantive obligations constitutes an unlawful act (onrechtmatige daad) under Article 1365 of the Civil Code because it violates the principles of pacta sunt servanda and good faith. Thus, the binding nature of an LoI is determined not by its label but by the substance and legal intent of the parties. This study contributes to the understanding that an LoI may function as a binding legal instrument and impose liability on parties who terminate it unilaterally without valid legal grounds.